2022
DOI: 10.3390/su14116863
|View full text |Cite
|
Sign up to set email alerts
|

The Official Website as an Essential E-Governance Tool: A Comparative Analysis of the Romanian Cities’ Websites in 2019 and 2022

Abstract: This paper aims to measure the quality of all Romanian cities’ websites in 2019 and 2022, before and after the disruptive event of COVID-19. Since the official websites are the core instrument of e-governance, the changes in the quality of Romanian cities’ websites reflect the changes in the development of urban e-governance in Romania. The COVID-19 lockdowns and contact restrictions and the moving of most activities into the online environment had the potential to impact the performance of Romanian cities’ we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It is essential to recognize the significance of online instruments not only from the perspectives of websites of the national parks, but also from the municipalities or local authorities or the DMOs for communicating with tourists, residents, and even other types of stakeholders. Research in a Romanian context revealed that, at best, websites provide links for locals and tourists, rarely for business owners, and never for specific demographics such as the elderly or young people, with limited options for citizens to complete administrative procedures exclusively online [93]. Other owned tools could be tourism apps created for the promoted area.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to recognize the significance of online instruments not only from the perspectives of websites of the national parks, but also from the municipalities or local authorities or the DMOs for communicating with tourists, residents, and even other types of stakeholders. Research in a Romanian context revealed that, at best, websites provide links for locals and tourists, rarely for business owners, and never for specific demographics such as the elderly or young people, with limited options for citizens to complete administrative procedures exclusively online [93]. Other owned tools could be tourism apps created for the promoted area.…”
Section: Discussionmentioning
confidence: 99%